Humerus Diaphysis Fracture in a Newborn during Vaginal Breech Delivery - Baris Kaya; Korkut Daglar; Ayse Kirbas; Abdullah Tüten (Case Reports in Obstetrics and Gynecology)
While most obstetricians are familiar with fracture of the clavicle in newborns during birth, an unlucky minority of obstetricians has encountered long-bone fractures in newborns as well. This complication is traumatic not only for the neonate, but also for the family and the obstetrician; it is also difficult to explain. Fortunately, the long-term prognosis for fracture of the long bones is excellent. Both vaginal and cesarean breech deliveries and maneuvers can be responsible for birth traumas, including long-bone fractures. This case report presents a newborn with breech presentation delivered vaginally that resulted in humerus diaphysis fracture.